THE INTEGRATED ACTION PLAN OF NATIONAL MALARIA ELIMINATION IN THAILAND: STUDY IN THE NORTH EAST AND THE EASTERN PART OF THAILAND - Sowat, Chantana; Srithongtham, Orathai; Wongphuka, Kanyarach; Sanguansat, Keinika; Manmanah, Direak; Wiangkham, Lapasrada; Sudathip, Prayuth; Kanjanasuwan, Jerdsuda; Promeiang, Praparat; Kitchakarn, Suravadee (Proceedings of the International Conference on Applied Science and Health, 2017)
Background: In 2024, the National Malaria Elimination Strategy proposed to eliminate indigenous malaria cases in all districts and expected that Thailand would be certified as free a malaria case areas before 2026. Even though the national malaria elimination policy focuses on accelerating malaria elimination in Thailand by improving diagnosis & treatment, intensifying active case detection, increasing ITN coverage and ensuring DOTs & follow up and Therapeutic Efficacy Surveillance. Aims: The objective of the study on the action plan of national malaria elimination in Thailand as the area study in the Northeast and the East of Thailand is to convince all partnerships to make integrated action plans. All provinces in the Northeast and the East of Thailand were selected with significant partnerships in transmission areas. Methods: Through the community participation and strategic planning workshops, an integrated process of data collection and analysis was undertaken and descriptively presented. Strengths, Opportunities, Aspirations and Results (SOAR) analysis was employed in the context of strategic planning of eliminating malaria cases from transmission areas. The registered partners in the workshop were divided into ten groups. In each working group, there were approximately 10-12 partners who were key persons and lived in the same community. Results: The findings showed that there were practically integrated action plans from significant partnerships in each transmission area. Twenty seven action plans of all provinces were presented to the provincial level for approval before being launched in their communities. Some outcomes from strongly launched action plans have been obviously regarded as the best practices of each province. Conclusion: The study suggested that in order to manage and to convince some key partners to join relevant malaria elimination activities, regular active participation at the national level, provincial level and community level by specifically focusing on sustainably maintaining malaria-free areas is needed. Local Administrative Organization support is also required to maintain the sustainability of the malaria- free areas in Thailand.Â